IRE1 signaling affects cell fate during the unfolded protein response - Lin, Jonathan H; Li, Han; Yasumura, Douglas; Cohen, Hannah R; Zhang, Chao; Panning, Barbara; Shokat, Kevan M; Lavail, Matthew M; Walter, Peter (Science (American Association for the Advancement of Science), 2007)
Endoplasmic reticulum (ER) stress activates a set of signaling pathways, collectively termed the unfolded protein response (UPR). The three UPR branches (IRE1, PERK, and ATF6) promote cell survival by reducing misfolded protein levels. UPR signaling also promotes apoptotic cell death if ER stress is not alleviated. How the UPR integrates its cytoprotective and proapoptotic outputs to select between life or death cell fates is unknown. We found that IRE1 and ATF6 activities were attenuated by persistent ER stress in human cells. By contrast, PERK signaling, including translational inhibition and proapoptotic transcription regulator Chop induction, was maintained. When IRE1 activity was sustained artificially, cell survival was enhanced, suggesting a causal link between the duration of UPR branch signaling and life or death cell fate after ER stress. Key findings from our studies in cell culture were recapitulated in photoreceptors expressing mutant rhodopsin in animal models of retinitis pigmentosa.